Kant and the Constitution of Russian Federation - Belov V. (Кантовский сборник, 2014)
This article is an attempt to give I. Kant “credit” for the Constitution of Russian Federation. Of course, the articles of Constitution require significant improvement so that they adhere to the letter and the spirit of Kant’s ideas on state and law. The article stresses the need to take into account two provisions of Kant’s philosophy: the complementarity of morals and law and support for traditional family values. The legal discussions on the essence of constitutionalism, supremacy of law, and constitutional state lack philosophical depth and consideration of the sources of these phenomena. Without a philosophical interpretation of the phenomenon of law, lawyers will be able to neither understand Kant’s “idealism”, nor explain the connection between this idealism and legal practice. The article presents two strategies corresponding to the spirit of Kant’s constitutional state in the modern Russian conditions: the principle of developing a moral (rather than competent) personality and the principle of population preservation. A necessary condition for the effectiveness of constitutional provisions is an increase in the moral and cultural level, which can be facilitated by examples of moral conduct shown by the authorities and changes in the educational policy. Thus, at the moment, the moral state of society — the moral climate and imperatives of public consciousness that largely affect the formation of personal morality — seems to be more important than a legal reform. Another important public strategy is orientation towards developing a selfreliant and moral personality, i. e. humanitarisation rather than juridification of education.